Faktor - Faktor yang Mempengaruhi Kinerja Keuangan Bank Perkreditan Rakyat - Putra, I Kadek Sardika; Hasibuan, Henny Triyana (E-Jurnal Akuntansi; Vol 31 No 9 (2021)DO - 10.24843/EJA.2021.v31.i09.p06, 2021)
This study aims to examine the effect of the Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) and Operational Efficiency Ratio (BOPO) variables on the financial performance of BPRs as proxied by ROA. The population in this study were all BPRs in Badung Regency which were registered with the Financial Services Authority (OJK) during the 2016-2018 period. Determination of the sample using purposive sampling method and obtained as many as 49 rural banks with a total of 147 observations. The analysis technique used is multiple linear regression analysis techniques. The results of this study indicate that the NPL and LDR variables have no effect on financial performance, while OEOI has a negative effect on financial performance. This research can add information and knowledge about the effect of NPL, LDR, OEOI on BPR financial performance as proxied by ROA. Keywords: ROA; NPL; LDR; BOPO.